Rapid and Complete Surface Modification with Strain‐Promoted Oxidation‐Controlled Cyclooctyne‐1, 2‐Quinone Cycloaddition (SPOCQ). (15th February 2017) - Sen, Rickdeb; Escorihuela, Jorge; van Delft, Floris; Zuilhof, Han
Abstract: Strain‐promoted oxidation‐controlled cyclooctyne‐1, 2‐quinone cycloaddition (SPOCQ) between functionalized bicyclo[6.1.0]non‐4‐yne (BCN) and surface‐bound quinones revealed an unprecedented 100 % conjugation efficiency. In addition, monitoring by direct analysis in real time mass spectrometry (DART‐MS) revealed the underlying kinetics and activation parameters of this immobilization process in dependence on its microenvironment.